KEMITRAAN PUBLIK – PRIVAT PT PASANGKAYU PADA KELURAHAN MARTAJAYA MELALUI PROGRAM AIR BERSIH - Apriliyani Apriliyani; Jerry Devano; Moh. Rahul Hi Sabollah; Rian Rachdiat Maka; Raihan Fathilah; Zulkifli Zulkifli (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This research aims to analyze the form of PT Pasangkayu's Public-Private Partnership in Mertajaya Village through the clean water program. This research uses qualitative research methods with data collection techniques through observation, interviews and documentation. Research informant, Head of Public Services, Mertajaya Village and Community. The results of this research show that the clean water program has been implemented since 2025 and is sustainable. PT Pasangkayu provides water reservoirs, pipe installations, and building materials such as bricks to strengthen clean water infrastructure.